Sandstone weathering, Electrical Resistivity Tomography, and the deterioration of San Rock Art in the Golden Gate Highlands National Park, South Africa - Mol, L (2011)
Electrical Resistivity Tomography (ERT) is a novel technique which can be used to build up a 2D pseudo-section of resistivity distribution of a porous material. Here, it is used to visualise internal moisture regimes by measuring the resistivity distribution of transects within sandstone, inferring that high resistivity equals low moisture content and vice versa. This method was used to perform two intermediate complexity laboratory tests; the first one to determine high-resolution, multi-scale drying patterns of sandstone, the second to determine capillary ingress of moisture within a sandstone block and the influence of temperature on moisture distribution. It was found that moisture behaviour showed far more complex patterns than previously acknowledged. A new model is therefore proposed which describes the influence of increased near-surface temperatures on capillary rise. This series of tests bridge the gap between field observations and mathematical models, as well as confirm the validity of ERT as a geomorphological tool. This research was continued by investigating the role of internal moisture in sandstone weathering using the Golden Gate Highlands National Park (GGHNP), South Africa as a case study. The ERT data was correlated with Equotip (rock surface hardness) and Protimeter (rock surface saturation) measurements. Seven sites were investigated, which showed that there is a non-linear correlation between rock surface hardness and internal moisture patterns. In addition, annual change measurements confirmed that the fluctuating patterns of internal moisture can be correlated to strengthening or weakening of the rock surface. This research therefore proposes two new conceptual weathering models. The first correlates ‘optimal moisture content’ to rock surface strength. The second correlates the development of shelters and changing weathering patterns to the non-linear interaction between case hardening and internal moisture. This new approach to sandstone weathering can be incorporated into conservation methods, as rock surface loss is one of the main causes of the San Rock Art deterioration observed in the GGHNP.